The Influence of Physiological Aging and Atrophy on Brain Viscoelastic Properties in Humans - Sack, Ingolf; Streitberger, Kaspar-Josche; Krefting, Dagmar; Paul, Friedemann; Braun, Jürgen (PloS one, 2011)
Physiological aging of the brain is accompanied by ubiquitous degeneration of neurons and oligodendrocytes. An alteration of the cellular matrix of an organ impacts its macroscopic viscoelastic properties which can be detected by magnetic resonance elastography (MRE)--to date the only method for measuring brain mechanical parameters without intervention. However, the wave patterns detected by MRE are affected by atrophic changes in brain geometry occurring in an individual's life span. Moreover, regional variability in MRE-detected age effects is expected corresponding to the regional variation in atrophy. Therefore, the sensitivity of brain MRE to brain volume and aging was investigated in 66 healthy volunteers aged 18-72. A linear decline in whole-brain elasticity was observed (-0.75%/year, R-square = 0.59, p<0.001); the rate is three times that determined by volume measurements (-0.23%/year, R-square = 0.4, p<0.001). The highest decline in elasticity (-0.92%/year, R-square = 0.43, p<0.001) was observed in a region of interest placed in the frontal lobe with minimal age-related shrinkage (-0.1%, R-square = 0.06, p = 0.043). Our results suggest that cerebral MRE can measure geometry-independent viscoelastic parameters related to intrinsic tissue structure and altered by age.